2013
DOI: 10.1053/j.jfas.2012.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Locating the Sural Nerve during Calcaneal (Achilles) Tendon Repair with Confidence: A Cadaveric Study with Clinical Applications

Abstract: The sural nerve is at risk of iatrogenic injury even during minimally invasive operative procedures to repair the calcaneal (Achilles) tendon. Through 107 cadaveric leg dissections, the data derived from the present study was used to develop a regression equation that will enable surgeons to estimate the intersection point at which the sural nerve crosses the lateral border of the Achilles tendon, an important surgical landmark. In most cases, the sural nerve crossed the lateral border of the Achilles tendon 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 42 publications
0
33
2
2
Order By: Relevance
“…A recent cadaver study reported that the sural nerve would crosses the lateral border of the Achilles tendon 8- to 10-cm proximal to the superior border of the calcaneal tuberosity in most cases [19]. Therefore, a surgeon can avoid injuring the sural nerve by doing all percutaneous procedures within 8 cm proximal to the calcaneal tuberosity.…”
Section: Introductionmentioning
confidence: 99%
“…A recent cadaver study reported that the sural nerve would crosses the lateral border of the Achilles tendon 8- to 10-cm proximal to the superior border of the calcaneal tuberosity in most cases [19]. Therefore, a surgeon can avoid injuring the sural nerve by doing all percutaneous procedures within 8 cm proximal to the calcaneal tuberosity.…”
Section: Introductionmentioning
confidence: 99%
“…Its utility stems from the fact that it is easy to find and harvest due to its usual location in the superficial fascia and just posterior to the lateral malleolus in close association with the small saphenous vein. Moreover, the sural nerve is vulnerable to damage following fracture of related bones (Bae, 2013) or surgical procedures such as incision, retraction, and suture during reconstruction of the Achilles tendon (Citak et al, 2007;Blackmon et al, 2013;Lee and Park, 2014). It is also subjected to biopsy (Ruth et al, 2005) or nerve conducting studies for the diagnosis of diseases such as diabetic neuropathy (Kwon et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It is also subjected to biopsy (Ruth et al, 2005) or nerve conducting studies for the diagnosis of diseases such as diabetic neuropathy (Kwon et al, 2000). Moreover, the sural nerve is vulnerable to damage following fracture of related bones (Bae, 2013) or surgical procedures such as incision, retraction, and suture during reconstruction of the Achilles tendon (Citak et al, 2007;Blackmon et al, 2013;Lee and Park, 2014). Likewise, nerve entrapment occasionally occurs at the site (Pringle et al, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…with Achilles Tendon and if any crossing of the nerve to medial side in relation to Achilles Tendon is of immense help for surgeons [9]. Accordingly, a view of previous studies at different level of Achilles Tendon in relation to Sural nerve along with observations made in the present study is assessed through following important parameters.…”
Section: Discussionmentioning
confidence: 86%